LEARNING ENGLISH SPEAKING BY USING SHORT STORY - Fitriani, Fitriani (FIKRUNA Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2019)
Abstract The purpose of English foreign teaching is to help students to communicate fluently in the target language cause many teachers still believe that an English foreign language class should focus on mastering linguistic element only. However, recent trend in English foreign language teaching indicates the necessity of integrating literature because of its rich potential to provide an authentic model of language use. Short story is one of literary to be the most suitable choice for this due to its potential to help students enhance the four skills-listening, speaking, reading and writing-more effectively because of the motivational benefit embedded in the stories. Short story can relax and fun way because reading short story can allow students to escape own lives for a moment and live in other situation that mean students who get some vocabularies from stories they can convey the content more confidently and positively.